2018
DOI: 10.1016/j.asej.2016.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of PQ in grid connected PV system using hybrid technique

Abstract: This paper proposed a hybrid technique based on power quality (PQ) enhancement in grid connected Photovoltaic (PV) system. The hybrid technique is the combined performance of both the Radial Basis Function Neural Network (RBFNN) and Proportional Integral (PI) controller. The primary intention of the proposed method is to predict the adaptive gain parameters for both the normal and abnormal environment in the grid side. In the proposed method, the RBFNN is trained with input parameters such as grid power variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…The assessment properties represent that the projected technique could be a favorable solution for PQ improvement of the PV systems under grid side faults, which is proficient over the other conventional techniques which is mentioned in below section. From the comparison derived from table II, it clearly shows that the THD of the proposed controller is much superior over the existing techniques [11] and [12]. It can determine that the projected technique effectively enhances the PQ of the grid-connected PV system compared to the conventional techniques.…”
Section: Simulation Results and Discussionmentioning
confidence: 88%
“…The assessment properties represent that the projected technique could be a favorable solution for PQ improvement of the PV systems under grid side faults, which is proficient over the other conventional techniques which is mentioned in below section. From the comparison derived from table II, it clearly shows that the THD of the proposed controller is much superior over the existing techniques [11] and [12]. It can determine that the projected technique effectively enhances the PQ of the grid-connected PV system compared to the conventional techniques.…”
Section: Simulation Results and Discussionmentioning
confidence: 88%
“…The above results concluded that KGMO based optimization technique is very effective in dynamic weather conditions and gives lesser harmonics compared to other techniques. From the table 2 and 3, it clearly shows that the THD of proposed controller is much superior over the existing techniques [16] and [17]. It can determine that the projected technique effectively enhances the PQ of the grid-connected PV system when related to the existing techniques.…”
Section: Fig 9 Thd Calculation Of Proposed Methodsmentioning
confidence: 87%
“…Sujatha, B. G., and G. S. Anitha [16] presented a hybrid method based on PQ improvement in grid integrated PV system. The joined performance of both the RBFNN and PI controller is established in this paper.…”
Section: Related Workmentioning
confidence: 99%
“…A continuous power flow parameter for both the regular and abnormal conditions is the main objective of the grid-related PV topology. Using grid parameters, the proposed control technique would produce power pulses of the inverter [22].…”
Section: Grid Connected Pvmentioning
confidence: 99%